THE EFFECT OF LCDS-BASED INTERACTIVE E-SCHOOLBOOK (ESB) AGAINST HOTS AND SCIENTIFIC ATTITUDE OF STUDENTS - Marsakha, Annisa Tasya; Suyatna, Agus; Herlina, Kartini (Universitas Tanjungpura, 2020)
This study was aimed to determine the effect of the use of LCDS-based interactive electronic schoolbook (ESB) on atomic nuclei material with a scientific approach to Higher Order Thinking Skill (HOTS) and scientific attitudes of students and to investigate the average HOTS value of students after both using interactive and non-interactive ESB. The research design was a Non-equivalent Control Group Design, involving students as the research subjects from one of the State High Schools in Kotabumi, with XII IPA 5 as an experimental class and XII IPA 4 as a control class. Data processing techniques were performed by T-test. The results of the HOTS pretest-posttest students in the experimental class revealed that the Sig. (2-Tailed) value was smaller than 0.05, which was equal to 0,000, indicating that there was an effect of the use of LCDS-based interactive ESB with a scientific approach to the material of the atomic nuclei on HOTS students. The test results of the differences in scientific attitudes of students between the two classes enclosed that the Sig. (2-Tailed) value of 0.001 was smaller than 0.05. This implied the great influence of the use of LCDS-based interactive ESB on the scientific attitude of students. HOTS results of students in both classes also obtained the Sig. (2-Tailed) value of 0,000, stating that there was a significant difference in the average N-gain HOTS value of students who learned with LCDS-based interactive ESB against the non-interactive model.